2020
DOI: 10.4094/chnr.2020.26.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Partnership between Nurses and Parents of Hospitalized Children and the Quality of Pediatric Nursing Care as Perceived by Nurses

Abstract: Purpose: This study investigated the relationship of the partnership between nurses and parents of hospitalized children with the quality of pediatric nursing care as perceived by pediatric nurses.Methods: A cross-sectional descriptive study was conducted among 90 nurses. The data collected were analyzed using the independent t-test and the Pearson correlation coefficient.Results: The level of partnership between nurses and parents showed significant differences by nurses’ age (t=2.22, <i>p</i>=.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Nurses' experience, in other words, nurses' careers, showed the greatest total effect on the quality of respect, explanation, and skillfulness. This result coincides with that of Yoo et al [14], which reported that the quality of nursing care is high for experienced nurses. The characteristics of nurses are reported to be closely related to the quality of nursing provided to hospitalized children [22].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nurses' experience, in other words, nurses' careers, showed the greatest total effect on the quality of respect, explanation, and skillfulness. This result coincides with that of Yoo et al [14], which reported that the quality of nursing care is high for experienced nurses. The characteristics of nurses are reported to be closely related to the quality of nursing provided to hospitalized children [22].…”
Section: Discussionsupporting
confidence: 92%
“…The program was reported as effective in terms of communication, mutual dependence, cooperation, information sharing, and careful and sensitive consideration [12]. The finding of this study was also similar to the results of Yoo et al [14], which reported that the higher the partnership between parents and nurses, the higher the quality of nursing care for hospitalized children. The result of this study was that nurse-parent partnership affected the quality of respect and kindness, among the four categories of quality of nursing care in pediatric units, in turn reflecting the fact that inpatient nursing ought to be based on FCC.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations